DISEMINASI ALAT PENGOLAHAN AIR SIAP MINUM, SANITASI PORTABEL, DAN PEMBENTUKAN TIM GARBARATA UNTUK PEMULIHAN SANITASI LINGKUNGAN PASCA BANJIR ACEH TAMIANG - zulfan arico; Meilandy Purwandito; T. Andi Fadly; Muslimah; Sri Jayanthi; Fauziani; Fitriani (Fakultas Teknik, Universitas Samudra, 2026)
This community service program aimed to accelerate clean-water and basic sanitation recovery for flood-affected residents in Bendahara District, Aceh Tamiang Regency. The activities included socialization, sanitation education, water-tank placement, clean-water distribution, hygiene kit and bottled-water delivery, Garbarata team formation, and monitoring. The program reached five villages by delivering ten 1,050-liter water tanks, 2,000 liters of clean water per village per day for 20 days, 540 hygiene kits, and 540 five-liter bottled-water gallons. The intervention strengthened temporary safe-water access, village coordination, and post-flood hygiene education.